Impact of depressive symptoms compared with manic symptoms in bipolar disorder: results of a U.S. community-based sample - Calabrese, Joseph R; Hirschfeld, Robert M A; Frye, Mark A; Reed, Michael L (The journal of clinical psychiatry, 2004)
In the present study, we assessed the functional impact of depressive versus manic symptoms in bipolar disorder. A survey comprising the Sheehan Disability Scale (SDS), the Social Adjustment Scale Self-Report (SAS-SR), the Mood Disorder Questionnaire (MDQ), and other questions was mailed to a representative subset of 4810 individuals (with or without bipolar disorder) from a U.S. population-based epidemiologic study conducted in 2001. Of the 3191 evaluable surveys returned, 593 respondents screened positive for bipolar disorder on the MDQ and/or reported a physician diagnosis of bipolar disorder. In the 4 weeks prior to the survey, subjects reported a mean of 12.4 days of depressive symptoms and 7.0 days of manic symptoms (p < .0001). The majority of days with depressive (79.8%) and manic (77.1%) symptoms were disruptive. Both total and mean scores on each domain of the SDS (work, social life, family life) reflect significantly greater impairment because of depressive versus manic symptoms during the 4 weeks prior to the survey (p < .0001). Among the 118 employed subjects who missed at least 1 day of work in the past month, more workdays were missed because of depressive versus manic symptoms (0.78 vs. 0.15, p < .004). For each domain of the SAS-SR, functional impairment was attributed significantly more often to depressive symptoms than manic symptoms (p < .0001). Similar results were observed for the 12 months preceding the survey. Self-reported depressive symptoms are more frequent than manic symptoms and cause greater disruption of occupational, family, and social functioning. These findings underscore the need to improve the recognition and management of bipolar depression.